Highly Efficient 2D NIR‐II Photothermal Agent with Fenton Catalytic Activity for Cancer Synergistic Photothermal–Chemodynamic Therapy. Issue 7 (20th February 2020) - Zhang, Qiuhong; Guo, Qiangbing; Chen, Qian; Zhao, Xiaoxu; Pennycook, Stephen J.; Chen, Hangrong
Abstract: Photothermal therapy (PTT) has emerged as a promising cancer therapeutic modality with high therapeutic specificity, however, its therapeutic effectiveness is limited by available high‐efficiency photothermal agents (PTAs), especially in the second near‐infrared (NIR‐II) biowindow. Here, based on facile liquid‐exfoliated FePS3 nanosheets, a highly efficient NIR‐II PTA with its photothermal conversion efficiency of up to 43.3% is demonstrated, which is among the highest reported levels in typical PTAs. More importantly, such Fe‐based 2D nanosheets also show superior Fenton catalytic activity facilitated by their ultrahigh specific surface area, simultaneously enabling cancer chemodynamic therapy (CDT). Impressively, the efficiency of CDT could be further remarkably enhanced by its photothermal effect, leading to cancer synergistic PTT/CDT. Both in vitro and in vivo studies reveal a highly efficient tumor ablation under NIR‐II light irradiation. This work provides a paradigm for cancer CDT and PTT in the NIR‐II biowindow via a single 2D nanoplatform with desired therapeutic effect. Furthermore, with additional possibilities for magnetic resonance imaging, photoacoustic tomography, as well as drug loading, this Fe‐based 2D material could potentially serve as a 2D "all‐in‐one" theranostic nanoplatform. Abstract : A highly efficient 2D NIR‐II photothermal agent (PTA) with a photothermal conversion efficiency of up to 43.3% is first developed based on facile liquid‐exfoliated FePS3 nanosheets, which is among the highest reported levels. More importantly, this novel PTA also shows remarkable Fenton catalytic activity, enabling superior synergistic photothermal–chemodynamic therapeutics along with excellent biocompatibility.